Design of Variable-Stiffness Bistable Composite Laminates and Their Application in Variable-Camber Wings - Hanqi Xie; Shujie Zhang; Yizhang Yang; Yang Zhou; Hongxiao Zhao (Aerospace, 2025)
The bistable laminated structure is widely used in many fields due to its unique deformation characteristics. In practical engineering, laminates under different structural constraints will exhibit different steady-state deformation characteristics. This study proposes a novel bistable laminated structure based on applying a variable-stiffness design to the deformation element. By adjusting the laying area of the metal layer in the variable-stiffness zone, the out-of-plane deformation and local curvature distribution can be changed to better meet application requirements. This study adopts the finite element numerical simulation method to systematically investigate the influence of geometric parameters, the proportion of metal layer edge length, and the number of layers on the deformation performance of bistable laminates. Considering the design of a flexible bistable variable-camber wing, the variable-stiffness design proposed in this study was adopted to coordinate the curvature distribution of laminates, making the cambered airfoil of the wing more uniform and smoother and improving aerodynamic efficiency. The research results not only provide new ideas for designing bistable laminates under complex constraints but also offer design references for the lightweight optimization and aerodynamic performance improvement of bistable morphing wings.